2019
DOI: 10.14202/vetworld.2019.1180-1187
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and molecular characterization of Mycobacterium bovis infection in camels (Camelus dromedarius) in the Delta region, Egypt

Abstract: Aim: This study aimed to determine the prevalence rates of Mycobacterium infection in camel sera collected before slaughter and gross lesion tissue collected at postmortem (PM) using enzyme-linked immunosorbent assay (ELISA), bacteriological culture, and polymerase chain reaction (PCR). In addition, serum samples from humans who had occupational contact with camels were tested by ELISA and sputum sample by culture. Materials and Methods: ELISA was performed on serum samples antemortem. In addition, bacteriolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Finally, there is a public health concern linked to the risk of transmission to humans (324)(325)(326)(327). Dromedary camel infection by Mycobacterium tuberculosis or Mycobacterium bovis was reported in several countries (328)(329)(330)(331)(332)(333)(334)(335)(336)(337)(338)(339)(340)(341). Another mycobacterium, Mycobacterium avium subsp.…”
Section: Burnetii Still Neglected In the Oie List Of Zoonotic Pathmentioning
confidence: 99%
“…Finally, there is a public health concern linked to the risk of transmission to humans (324)(325)(326)(327). Dromedary camel infection by Mycobacterium tuberculosis or Mycobacterium bovis was reported in several countries (328)(329)(330)(331)(332)(333)(334)(335)(336)(337)(338)(339)(340)(341). Another mycobacterium, Mycobacterium avium subsp.…”
Section: Burnetii Still Neglected In the Oie List Of Zoonotic Pathmentioning
confidence: 99%
“…Specifically, M. bovis was reported in a cat and a mongoose in Turkey [ 16 ] and Egypt [ 17 ], respectively. A deer infected with BTB was also observed in Iran [ 18 ], while M. bovis was detected in camels and pigs in Egypt [ 19 , 20 ].…”
Section: Epidemiology Of Mycobacterium Bovis In Th...mentioning
confidence: 99%
“…In Egypt, M. bovis was recorded in a mongoose, 90 camels and pigs. 91 Numerous research revealed that the prevalence in Egypt was between 0.1% 92 and 16.4%. 93 Furthermore, studies with limited population sizes revealed a greater incidence, ranging from 22.2% (ref.…”
Section: Risk Factors and Prevalence Of M Bovis In...mentioning
confidence: 99%